Administrative proceedings adaptation to security challenges under martial law (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The constitutional right to judicial protection is inalienable and inviolable, and the inadmissibility of suspending the functioning of the judiciary and, at the same time, permanent threats to the security of participants to the judicial process, hostilities on the territory of the State and other destructive changes require a prompt response to ensure the uninterrupted conduct of judicial proceedings and create a safe environment for this. Therefore, there is a need for an in-depth analysis of the impact of the security aspect on the organisation and functioning of the administrative justice mechanism under martial law, and this is the purpose of the article. The subject of the study is the security barriers to the functioning of administrative courts and the ways to neutralise these barriers. The methodological basis of the study is the integrated use of the principles and means of general scientific methods of scientific knowledge (methods of system analysis, synthesis, induction and deduction), as well as certain methods of private and special scientific groups, in particular, statistical, comparative and dogmatic methods.The main security barriers to the administration of justice in the context of permanent threats of shelling are identified, in particular, such barriers include difficulties in physical access to courts, given the close proximity to the contact line, and the inability to organise a fully secure environment during the consideration of administrative cases. The attention is focused on the regulation of the process of participation in a court hearing via videoconference and the peculiarities of practical implementation of this opportunity in administrative proceedings. The author concludes that expanding the possibilities of safe administration of justice by improving e-justice or creating tools which will facilitate greater access to justice and protect the right to ensure the safety of life and health of each participant to the court proceedings is an urgent and priority task.
Keywords: administrative proceedings; security barriers; videoconference meetings; martial law; electronic justice.